Materialismo evolutivo : natureza, dialética e sujeito - Marques, Victor Ximenes (2014)
Evolutionary materialism is a proposal for a naturalistic metaphysics that seeks to combine the immanent teleology of Hegelian dialectics with non-teleological historicity of Darwinian evolution. Drawing upon more in biology than in physics to develop a general ontology, it discards the postulates of classical atomistic materialism to produce a new image of nature, one that is compatible with the objective existence of normativity and intentionality, facilitating an articulation between image manifest and scientific image. Evolutionary materialism attempts to understand subjectivity as natural reality, and to think how it is possible that it evolved over time out of a non-mental physical world. It seeks to understand the intelligence and rationality as a result, not as principles - as late and contingent products of a natural history. In order to do that, we mobilize theoretical tools from dialectical philosophy and from contemporary biology, and thus build a conceptual framework rich enough to allow for the naturalization of agency. Our goals are: 1) to argue that it is no longer possible to make progress on some classic questions of philosophy without a serious engagement with the natural sciences, 2) to show that there is a continuous historical line from Kant, through Hegel and the dialectical materialism, to recent scientific proposals that characterize life by its circular organization, and 3) to demonstrate that the formula Hegel + Darwin remains relevant and fruitful as the basis for a creative materialism, a research program seeking to naturalize the subject without eliminating it.